2017
DOI: 10.1111/apa.14063
|View full text |Cite
|
Sign up to set email alerts
|

Failing to meet relative humidity targets for incubated neonates causes higher heat loss and metabolic costs in the first week of life

Abstract: RH from day 1 to 8 was below the recommended target value for preterm infants and resulted in high evaporative and greater total BHL and additional metabolic cost. The findings pose numerous challenges, including nursing care and incubator design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Some researchers have suggested optimal relative humidity values that take account of the newborn infant gestational age at birth and postnatal age; both of which significantly influence transepidermal water loss 42 . These values of relative humidity were analysed in an observational study and confirmed with analytical calorimetry: there was an additional energy cost when the values set on the incubator deviated from the reference values 43 …”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Some researchers have suggested optimal relative humidity values that take account of the newborn infant gestational age at birth and postnatal age; both of which significantly influence transepidermal water loss 42 . These values of relative humidity were analysed in an observational study and confirmed with analytical calorimetry: there was an additional energy cost when the values set on the incubator deviated from the reference values 43 …”
Section: Resultsmentioning
confidence: 75%
“…42 These values of relative humidity were analysed in an observational study and confirmed with analytical calorimetry: there was an additional energy cost when the values set on the incubator deviated from the reference values. 43 Skin-to-skin contact is not a strategy for preventing water loss per se. However, during skin-to-skin contact, the newborn infant is placed in a microenvironment between the adult's skin and a garment or covering providing clothing isolation and reducing water loss to zero.…”
Section: How Can Water Losses Be Limited?mentioning
confidence: 99%
“…The addition of vapor to the ambient air of modern neonatal intensive care incubators to high levels of RH (>80%), results in an IWL that corresponds to that of a 3-4 weeks more mature infant nursed at medium RH (40-50%), thus reducing fluid requirements and simplifying management. Since evaporation also implies loss of heat, humidifying the incubator air also reduces heat loss as long as the care environment remains unperturbed [26].…”
Section: Iwl In Relation To Ambient Relative Humidity (Rh)mentioning
confidence: 99%